THE APPLICATION OF LEARNING MODEL: SNOW BALL THROWING ON THE LEARNING MATERIAL: TYPES OF HEAVY EQUIPMENTS ON THE CONSTRUCTION WORK IN THE CLASS X OF BUILDING MODELLING AND INTERIOR DESIGN AT SMK NEGERI 1 PALANGKA RAYA - Oktaria; Lola Cassiophea (Jurusan Pendidikan Teknologi Dan Kejuruan, 2019)
The results of observations made at SMK Negeri 1 Palangka Raya and interviews with teachers who teach Building Construction showed that the grade of students in the learning material: Types of Heavy Equipment in The Construction Work of the academic year 2016/2017 is on average of 65% which is still below the minimum completeness criteria (KKM) 70. The purpose of this study is to determine student learning outcomes after the application of the Snowball Throwing type of Cooperative Learning Model. The design of this study uses descriptive research. Quantitative data in the form of numbers or grades obtained from student learning outcomes tests. This research was conducted from March 2018 to April 2018 at SMK Negeri-1 Palangka Raya. The population of all students in class X of Building Modeling and Interior Design at SMK Negeri-1 Palangka Raya of the year 2017-2019 was 33 students. The instrument used is the final test of student learning outcomes with 50 test questions. Each final test item was reviewed by three rater members, consisting of two lecturers from the University of Palangka Raya Civil Engineering Education Study Program and one teacher from the foundation of building construction in class X Building Modeling and Interior Design at SMK 1 Palangka Raya to get the validity of the instruments. Data analysis uses individual completeness and classical completeness. The results showed that overall learning activities in the meeting I to VI were carried out well and student learning outcomes had reached completeness criteria that had increased and decreased. On the first meeting until the last meeting, it was found that learning completeness was 21.21%, 21.21%, 62.5%, 78.125%, 81.25%, 81.81% and the achievement level was 65%, 65%, 71%, 73%, 77%, 81% with criteria achieved. While the results of the final test analysis obtained complete student learning completeness of 87.87% and achievement rate of 72% with criteria achieved. Thus it can be concluded by using the type of Cooperative Learning model Snowball Throwing on the learning material: Types of Heavy Equipment in Construction Work Class X Building Modeling and Interior Design in the SMK Negeri-1 Palangka Raya academic year 2017/2018, the learning results were better than the conventional method.